Estimation of Nitrogen Content Using Green Normalized Difference Vegetation Index (GNDVI) in Sugarcane: Estimasi Kandungan Nitrogen Menggunakan Metode Green Normalized Difference Vegetation Indeks (GNDVI) di Tanaman Tebu - Daffa Dhiya Ulhaq; Sari Virgawati (Jurnal Ilmu Tanah dan Air, 2025)
Sugarcane is one of the most widely cultivated plantation crops in Indonesia, but production has declined, particularly in Kapanewon Sedayu, Bantul, due to a suspected nitrogen deficiency. Nitrogen is required for the formation of buds, leaves, and stems. GNDVI is a vegetation index that is more sensitive to chlorophyll content. This study aims to determine the correlation between GNDVI and the nitrogen content of sugarcane tissue based on drone imagery, to develop an estimation model, and to produce an N-content map. The research was conducted at the Gunung Ombo Plantation, Argomulyo, Sedayu, Bantul, Yogyakarta, using a quantitative descriptive method. Forty-five sample points were established (30 for prediction and 15 for reference). Leaf samples were collected from the third leaf sheath of 5-month-old sugarcane and analyzed for nitrogen content using the Kjeldahl method. The relationship between GNDVI and tissue nitrogen was examined using Pearson’s correlation, linear regression, and paired t-tests. Results showed a strong correlation (r = 0.896) with a coefficient of determination (R² = 0.7891) and the regression equation y = 4.7507x + 0.6012. The paired t-test indicated no significant difference between predicted and reference nitrogen values. The resulting estimation map can support nitrogen fertilization management in sugarcane cultivation in the study area.